2018
DOI: 10.15829/1728-8800-2018-3-33-37
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Probability of the Long Term Fatal Outcome of Stroke by the Data of Territory and Populational Registry

Abstract: Aim. To develop a prediction model of individual probability of long term (within first 28 days from the onset) outcome of stroke.Material and methods. By the method of territory-populational registry, in 2009-2016 in 16 regions of Russia, an analysis performed, of significant predictors of fatal stroke outcome. Overall, 50902 strokes registered in persons older 25 y. In 1553 there were no data on long term mortality. By the results of revealed significant predictors of the fatal outcome of stroke by LOTUS met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…Но, как показывают реалии, большинство анестезиологов-экспертов мало задумывается об этом. Решения принимаются скорее интуитивно или порой даже на эмоциональном уровне, хотя необходимо рассчитывать вероятность летального исхода по формуле Байеса или приводить статистику летального исхода конкретного заболевания [2].…”
unclassified
“…Но, как показывают реалии, большинство анестезиологов-экспертов мало задумывается об этом. Решения принимаются скорее интуитивно или порой даже на эмоциональном уровне, хотя необходимо рассчитывать вероятность летального исхода по формуле Байеса или приводить статистику летального исхода конкретного заболевания [2].…”
unclassified
“…It has been revealed that recurrent IS is characterized by more severe course, accompanied by higher level of neurological deficiency and it is the common reason of severe cognitive impairments, which makes this problem extremely relevant in the medical, social and economic aspects [1][2][3][4]. Development of differentiated approach, which includes individual prognosis, is the optimal management strategy for increase the effectiveness of treatment patients with IS [5]. Numerous studies have found that the leading factors which influence the stroke outcome are: the age of the patient, the initial level of neurological deficits, infarct volume, the severity of the dislocation syndrome, and the presence of decompensated somatic pathology [6,7].…”
mentioning
confidence: 99%